Sustainability Differences and Balanced Development Countermeasures of School Buildings in Urban and Rural Areas of Chengdu - Zhang Yunfei; Chiang Jeffrey C.L. (E3S Web of Conferences)
As green and environmental protection concepts become increasingly popular, sustainable construction is an important development trend and direction in the construction industry. In recent years, sustainable buildings in various fields in China have developed rapidly. However, due to the differences in economic and cultural development between urban and rural areas, there is still a significant gap in the sustainability level of urban and rural buildings. The sustainability disparity between urban and rural school buildings in China was studied in this paper. In the study, taking Chengdu, Sichuan Province as an example, a series of investigations and studies were carried out. The differences in sustainability levels and characteristics of urban and rural school buildings were sorted out and analysed in detail, and countermeasures and suggestions for the balanced development of sustainable urban and rural school buildings were proposed. This study has a certain promoting effect and reference value for improving the architectural sustainability in China’s education sector and the balanced development of sustainable buildings in urban and rural schools.